The Phylogenetic Intrarelationships of Spiny-Rayed Fishes (Acanthomorpha, Teleostei, Actinopterygii): Fossil Taxa Increase the Congruence of Morphology with Molecular Data - Davesne, Donald; Gallut, Cyril; Barriel, Véronique; Janvier, Philippe; Lecointre, Guillaume; Otero, Olga (Frontiers in Ecology and Evolution, 2016)
Acanthomorpha (spiny-rayed fishes) is a clade of teleosts that includes more than 15 000 extant species. Their deep phylogenetic intrarelationships, first reconstructed using morphological characters, have been extensively revised with molecular data. Moreover, the deep branches of the acanthomorph tree are still largely unresolved, with strong disagreement between studies. Here, we review the historical propositions for acanthomorph deep intrarelationships and attempt to resolve their earliest branching patterns using a new morphological data matrix compiling and revising characters from previous studies. The taxon sampling we use constitutes a first attempt to test all previous hypotheses (molecular and morphological alike) with morphological data only. Our sampling also includes Late Cretaceous fossil taxa, which yield new character state combinations that are absent in extant taxa. Analysis of the complete morphological data matrix yields a new topology that shows remarkable congruence with the well-supported molecular results. Lampridiformes (oarfishes and allies) are the sister to all other acanthomorphs. Gadiformes (cods and allies) and Zeiformes (dories) form a clade with Percopsiformes (trout-perches) and the enigmatic Polymixia (beardfish) and Stylephorus (tube-eye). Ophidiiformes (cusk-eels and allies) and Batrachoidiformes (toadfishes) are nested within Percomorpha, the clade that includes most of modern acanthomorph diversity. These results provide morphological synapomorphies and independent corroboration of clades previously only recovered from molecular data, thereby suggesting the emergence of a congruent picture of acanthomorph deep intrarelationships. Fossil taxa play a critical role in achieving this congruence, since a very different topology is found when they are excluded from the analysis.